Radiological Issues for Fukushima’s Revitalized Future 2016
DOI: 10.1007/978-4-431-55848-4_4
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mass Spectrometry for Analysis of Cesium and Strontium in Environmental Samples Obtained in Fukushima Prefecture

Abstract: For the assessment of Fukushima Daiichi Nuclear Power Plant accident, the applicability of the thermal ionization mass spectrometry (TIMS), which is a type of mass spectrometry, was studied. For the study of the recovery/analysis method of cesium and strontium, at first, the radioactive cesium and strontium were generated by the irradiation of natural uranium at KUR. After this study, the applicability of this method to the environmental samples obtained in Fukushima prefecture was verified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 19 publications
(26 reference statements)
0
19
1
Order By: Relevance
“…They analyzed the isotopic composition of Cs in rainwater, plant samples, and soil samples: rainwater and soil samples were analyzed by ICP-MS [1,5,6], and plant samples were analyzed by TIMS [2][3][4]. These results showed that the 135 Cs/ 137 Cs isotopic ratio in the environmental samples obtained in/around Fukushima prefecture was different from that of GF and the Chernobyl Nuclear Power Plant (CNPP).…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…They analyzed the isotopic composition of Cs in rainwater, plant samples, and soil samples: rainwater and soil samples were analyzed by ICP-MS [1,5,6], and plant samples were analyzed by TIMS [2][3][4]. These results showed that the 135 Cs/ 137 Cs isotopic ratio in the environmental samples obtained in/around Fukushima prefecture was different from that of GF and the Chernobyl Nuclear Power Plant (CNPP).…”
Section: Introductionmentioning
confidence: 93%
“…These results showed that the 135 Cs/ 137 Cs isotopic ratio in the environmental samples obtained in/around Fukushima prefecture was different from that of GF and the Chernobyl Nuclear Power Plant (CNPP). In addition, Shibahara et al determined the 134 Cs/ 137 Cs activity ratio in plant samples using TIMS, suggesting that 2D analysis of radioactive Cs was useful for source analysis [2][3][4].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations